FORMALIZATION OF DATA SPACE USING THE ALGEBRAIC SYSTEM - Shakhovska, N. B. (Radio Electronics, Computer Science, Control, 2010)
Problems of different sources data processing are analyzed. A formal data space model and operations performed in it are described.